Curative Effects of ZHENG-Based Fuzheng-Huayu Tablet on Hepatitis B Caused Cirrhosis Related to CYP1A2 Genetic Polymorphism. (24th October 2013) - Li, Qing-Ya; Guo, Zhi-Zhong; Deng, Xin; Xu, Lie-Ming; Gao, Yue-Qiu; Zhang, Wei; Wang, Xiao-Su; Xue, Dong-Ying; Lu, Yi-Yu; Liu, Ping; Su, Shi-Bing
Abstract : Aim . To investigate the correlation of Fuzheng-Huayu tablet (FZHY) efficacy on chronic hepatitis B caused cirrhosis (HBC) and single nucleotide polymorphisms (SNPs) of CYP1A2. Methods . After 111 cases of HBC with 69 excess, 21 deficiency-excess, and 21 deficiency ZHENGs (ZHENG, also called traditional Chinese medicine syndrome) were treated by FZHY for 6 months, clinical symptoms, Child-Pugh score, and ZHENG score were observed. Three of the SNPs in CYP1A2 gene were detected and analyzed using SNaPshot assay. Results . In ZHENG efficacy between effective and invalid groups, there was significant difference (P < 0.001 ). The ZHENG deficiency was significantly correlated with FZHY efficacy (P < 0.05 ). AA genotype of CYP1A2-G2964A was significantly different with GG genotype (P < 0.05 ) between CYP1A2 Genotypes and FZHY efficacy on ZHENG. More importantly, GA plus AA genotype of CYP1A2-G2964A was significantly different with deficiency ZHENG (P < 0.05 ) between CYP1A2 genotypes and FZHY efficacy on ZHENG. Conclusion . FZHY improved ZHENG score of HBC, and these efficacies may relate to CYP1A2-G2964A sites. It was suggested that CYP1A2-G2964A locus is probably a risk factor for ZHENG-based FZHY efficacy in HBC.